2005
DOI: 10.5194/angeo-23-1391-2005
|View full text |Cite
|
Sign up to set email alerts
|

Electric current and magnetic field geometry in flapping magnetotail current sheets

Abstract: Abstract. Using four-point magnetic field measurements by the Cluster spacecraft, we statistically analyze the magnetic field and electric current configurations during rapid crossings of the current sheet observed in July-October 2001 at geocentric distances of 19 R E . The database includes 78 crossings, specially selected to apply multi-point data analysis techniques to calculate vector derivatives. Observed bipolar variations of j z , often with |j z |>j y , indicate that the electric currents follow kinks… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

21
245
0
5

Year Published

2005
2005
2014
2014

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 192 publications
(276 citation statements)
references
References 35 publications
21
245
0
5
Order By: Relevance
“…A schematic view of this wave is shown in Fig. 4 based on this study and earlier observations (Zhang et al, 2002;Sergeev et al, 2004;Runov et al, 2005b). In order to estimate the amplitude of this wave, we performed a detailed analysis of each Cluster neutral sheet crossing by calculating the Cluster tetrahedron barycenter transverse distance from the neutral sheet (Runov et al, 2005a).…”
Section: Discussionmentioning
confidence: 80%
See 4 more Smart Citations
“…A schematic view of this wave is shown in Fig. 4 based on this study and earlier observations (Zhang et al, 2002;Sergeev et al, 2004;Runov et al, 2005b). In order to estimate the amplitude of this wave, we performed a detailed analysis of each Cluster neutral sheet crossing by calculating the Cluster tetrahedron barycenter transverse distance from the neutral sheet (Runov et al, 2005a).…”
Section: Discussionmentioning
confidence: 80%
“…The magnetotail neutral sheet is anchored to the geomagnetic dipole at a hinging distance of 11 Re (Dandouras, 1988). As mentioned in the introduction, the neutral sheet kink-like wave along the Y-axis has been observed at tailward distances of ∼14 to 30 Re (Lui et al, 1978;Runov et al, 2005b). The present study shows that this wave can be observed as close to the Earth as 11 Re along the X direction, in the neighbourhood of the magnetotail hinge point.…”
Section: Discussionmentioning
confidence: 83%
See 3 more Smart Citations